1985
DOI: 10.1159/000138106
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Oral Penicillin before and after Gastroplasty for Morbid Obesity

Abstract: Gastroplasty for morbid obesity results in a small proximal pouch with a narrow stoma to the distal stomach. Absorption of phenoxymethylpenicillin given in tablets and liquid form was evaluated in 8 females before and 3 months after gastroplasty. Penicillin absorption was not affected to any significant extent. Oral penicillin can therefore safely be given for the treatment of infections in patients after gastroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The latter may particularly be of relevance for drugs for which altered pharmacokinetics in obese patients compared to non-obese patients have been reported, or when the pharmacodynamics are different in obese individuals as is the case for VKAs or platelet inhibitors. We note that even for similar drugs, different results may be observed, as shown for phenoxymethylpenicilin 54,55 . Also for controlled release formulations, conflicting results were obtained in different studies 41,42 .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The latter may particularly be of relevance for drugs for which altered pharmacokinetics in obese patients compared to non-obese patients have been reported, or when the pharmacodynamics are different in obese individuals as is the case for VKAs or platelet inhibitors. We note that even for similar drugs, different results may be observed, as shown for phenoxymethylpenicilin 54,55 . Also for controlled release formulations, conflicting results were obtained in different studies 41,42 .…”
Section: Discussionmentioning
confidence: 64%
“…Terry et al and Miskowiak et al, describe the pharmacokinetics of oral phenoxymethylpenicillin after gastroplasty and jejunoileal bypass, procedures that are to date not often applied any more 54,55 . Miskowiak et al reported no significant changes of gastroplasty on the absorption and concentrations of phenoxymethylpenicillin when given as a non-coated tablet or as an aqueous solution (one-week washout) in eight female bariatric surgery patients before and three months after gastroplasty surgery 54 . There were also no significant differences in AUC between tablet and aqueous solution.…”
Section: Beta-lactam Antibiotics (Amoxicillin Penicillin and Ampicillin)mentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies, i.e. Terry et al and Miskowiak et al, describe the pharmacokinetics of oral phenoxymethylpenicillin after gastroplasty and jejunoileal bypass, procedures that are to date not often applied any more 44,45 . Miskowiak et al evaluated the effect of gastroplasty on the absorption of phenoxymethylpenicillin when given as a non-coated tablet or as an aqueous solution (one-week washout) in eight female bariatric surgery patients before and three months after gastroplasty surgery.…”
Section: Beta-lactam Antibiotics (Amoxicillin Penicillin and Ampicillin)mentioning
confidence: 99%
“…In this study, no significant changes in plasma concentrations, Cmax, T1/2, Tmax and AUC were found before versus after surgery. 44 . There were also no significant differences in AUC between tablet and aqueous solution.…”
Section: Beta-lactam Antibiotics (Amoxicillin Penicillin and Ampicillin)mentioning
confidence: 99%